The amino acids motif-32GSSYN36-in the catalytic domain of E. coli flavorubredoxin NO reductase is essential for its activity - Martins, Maria C. (2021)
Funding Information: Funding: This study was financially supported by the Portuguese Fundação para a Ciência e Tec-nologia (FCT), grants PTDC/BIA-BQM/27959/2017 and PTDC/BIA-BQM/0562/2020, and Project MOSTMICRO-ITQB with references UIDB/04612/2020 and UIDP/04612/2020. This project has also received funding from the European Union’s Horizon 2020 research and innovation program under grant agreement 810856. MCM is the recipient of FCT grant SFRH/BD/143651/2019. BAS is the recipient of FCT grant DFA/BD/8066/2020. Funding Information: This study was financially supported by the Portuguese Funda??o para a Ci?ncia e Tecnologia (FCT), grants PTDC/BIA-BQM/27959/2017 and PTDC/BIA-BQM/0562/2020, and Project MOSTMICRO-ITQB with references UIDB/04612/2020 and UIDP/04612/2020. This project has also received funding from the European Union?s Horizon 2020 research and innovation program under grant agreement 810856. MCM is the recipient of FCT grant SFRH/BD/143651/2019. BAS is the recipient of FCT grant DFA/BD/8066/2020. Publisher Copyright: © 2021 by the authors. Licensee MDPI, Basel, Switzerland.